Students’ Critical Thinking Skills in The Reflective Class of Islamic Cultural History - Suntiah, Ratu (Jurnal Pendidikan Islam, 2021)
This study investigates students’ critical thinking skills in the subject of Islamic Cultural History, built within reflective teaching. It applied qualitative method using descriptive analytic. The study involved students from Class-XI aged 16-17 years old in MAN 1 and MAN 2 in Bandung, West Java, Indonesia. The data were collected using observation and documentation for the contemplative teaching and learning process. The data then were analysed using Miles and Hubermen covering data reduction, presentation, and conclusion. The results show that the reflective class supported the students’ learning development and their critical thinking. The students prepared well for learning, engaged in the learning activities, contributed to the discussion, and enthusiastically compiled personal journals. When it comes to their critical thinking development, the students showed their progressive capacities in building their ideas, evaluating theirs and others’ arguments and working together to solve problems.